Mechanical, fluoride release, and antibacterial performance of waste-derived glass ionomer cements - Loh, Zhi Wei; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Ahmad Khiri, Mohammad Zulhasif; Cheong, Wei Mun; Foong, Phey Yee (Elsevier Editora, 2025)
The demand for sustainable and cost-effective dental restorative materials is growing, particularly those capable of delivering both mechanical durability and long-term bioactivity. While conventional glass ionomer cements (GICs) offer fluoride release and biocompatibility, their mechanical limitations and reliance on virgin raw materials remain concerns. This study introduces a novel approach by synthesizing GICs from recycled calcium fluoroaluminosilicate (CFAS) glass derived from glass and clamshell wastes. GIC samples were aged up to 28 days and systematically evaluated. Among the formulations, GIC-CS5 exhibited the best performance, achieving a Vickers microhardness of 275 HV and a compressive strength of 119 MPa, exceeding the ISO 9917 minimum requirement of 50 MPa. Ion chromatography revealed sustained fluoride ions ranging from 36 to 124 ppm, supporting enamel remineralization and caries prevention. Antibacterial tests against Streptococcus mutans showed average inhibition zones ranging from 18 to 33 mm, highlighting their potential in suppressing bacterial proliferation. These results demonstrate that waste-derived GICs can achieve competitive performance benchmarks while supporting environmental sustainability and resource efficiency in dental material development.